1996
DOI: 10.1146/annurev.psych.47.1.205
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Social and Organizational Psychology

Abstract: This review considers recent theoretical and empirical developments in cross-cultural studies within social and organizational psychology. It begins with a description of the importance and the difficulties of universalizing psychological science. It then continues with an examination of theoretical work on both the internal-proximal and the external-distal constraints that mediate culture's influence on behavior. Influences on social cognition are documented by describing research on self-concept, self-esteem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(141 citation statements)
references
References 166 publications
6
130
0
4
Order By: Relevance
“…Benlik konusunun ele alındığı birçok çalışmada benlik batılı bir kavramsallaştırmayla ele alınmış (Bond and Smith, 1996) ve bu çalışmalarda "özerklik" ve "ilişkisellik" zıt kutuplar olarak değerlendirilmiştir (Kağıtçıbaşı, 2005). Yakın zamanda araştırmacılar benlik kurguları ile ilgili farklı tanılamaya gitmiş; ikili benlik kurgusu yapısından daha ziyade üçlü benlik yapısı ön plana çıkmıştır.…”
Section: Benlik Kurgusuunclassified
“…Benlik konusunun ele alındığı birçok çalışmada benlik batılı bir kavramsallaştırmayla ele alınmış (Bond and Smith, 1996) ve bu çalışmalarda "özerklik" ve "ilişkisellik" zıt kutuplar olarak değerlendirilmiştir (Kağıtçıbaşı, 2005). Yakın zamanda araştırmacılar benlik kurguları ile ilgili farklı tanılamaya gitmiş; ikili benlik kurgusu yapısından daha ziyade üçlü benlik yapısı ön plana çıkmıştır.…”
Section: Benlik Kurgusuunclassified
“…One of the often-cited problems in the interpretation of cross-cultural differences is the lack of comparability of testing methods (Bond & Smith, 1996). Indeed, achieving such comparability can seem like a daunting task, considering that over 50 types of equivalence have been discussed in the literature (for an excellent review, see Johnson, 1998).…”
Section: Measurement: Achieving Equivalencementioning
confidence: 99%
“…Previous cross cultural research has found that collectivist cultures (e.g., Singapore) tend to emphasize group needs over individual needs, to use more formalized rules (Hofstede, 1994;Triandis, 1995) and to require greater conformity from members (Bond and Smith, 1996) than individualist cultures. Collectivists also live in cohesive and tightly bounded groups which restrict mobility, especially upward mobility (Hofstede, 1991(Hofstede, , 1994.…”
Section: The Moderating Role Of Culture In Boundary Permeabilitymentioning
confidence: 99%